Unveiling the Genetic Landscape of Coronary Artery Disease Through Common and Rare Structural Variants - Kruthika R. Iyer; Shoa L. Clarke; Rodrigo Guarischi‐Sousa; Ketrin Gjoni; Adam S. Heath; Erica P. Young; Nathan O. Stitziel; Cecelia Laurie; Jai G. Broome; Alyna T. Khan; Joshua P. Lewis; Huichun Xu; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Genome‐wide association studies have identified several hundred susceptibility single nucleotide variants for coronary artery disease (CAD). Despite single nucleotide variant‐based genome‐wide association studies improving our understanding of the genetics of CAD, the contribution of structural variants (SVs) to the risk of CAD remains largely unclear. Method and Results We leveraged SVs detected from high‐coverage whole genome sequencing data in a diverse group of participants from the National Heart Lung and Blood Institute's Trans‐Omics for Precision Medicine program. Single variant tests were performed on 58 706 SVs in a study sample of 11 556 CAD cases and 42 907 controls. Additionally, aggregate tests using sliding windows were performed to examine rare SVs. One genome‐wide significant association was identified for a common biallelic intergenic duplication on chromosome 6q21 (P=1.54E‐09, odds ratio=1.34). The sliding window‐based aggregate tests found 1 region on chromosome 17q25.3, overlapping USP36, to be significantly associated with coronary artery disease (P=1.03E‐10). USP36 is highly expressed in arterial and adipose tissues while broadly affecting several cardiometabolic traits. Conclusions Our results suggest that SVs, both common and rare, may influence the risk of coronary artery disease.